PEMECAHAN DORMANSI BENIH KELAPA SAWIT DENGAN METODE DRY HEAT TREATMENT DAN PEMBERIAN GIBERELIN - Nuraini, Anne; Pangaribuan, Ikhwan Fadli; Suherman, Cucu (Jenderal Soedirman University, 2016)
Oil palm is a plant that has a long seed dormancy period. The existence of barrier on the seed coat causesdisturbance on imbibition so the process of germination of oil palm seed is hampered. This study aimed todetermine the effect of interaction between the heat treatment by dry-heat treatment method and the submersionof growth regulator gibberellin on oil palm dormancy breaking. The experiment was conducted using a factorialrandomized block design with 2 factors, i.e. 3 levels of dry-heat treatment duration (40 days, 50 days, 60 days)and 3 levels of gibberellin concentration (0 ppm, 100 ppm, 200 ppm) and repeated 3 times. The result showed thatno interaction between the duration of dry heat treatment and concentration of gibberellin on breaking the oilpalm dormancy. Treatment of dry heat treatment of 50 and 60 days had a good effect on percentage of germination,vigor index, radicle length and plumule length. Concentration of 100 and 200 ppm gibberellin had a good effecton percentage of germination, vigor index, radicle length and plumule length. Fifty days-period of dry heattreatment and concentration of 100 ppm gibberellin gave more effective effect than other treatment.Key words : dormancy, Dry-Heat Treatment, gibberellin, oil palmÂ ABSTRAKKelapa sawit merupakan tanaman yang memiliki masa dormansi benih yang panjang. Adanya penghalangkulit benih menyebabkan proses imbibisi menjadi terganggu sehingga proses perkecambahan benih kelapa sawitterhambat. Penelitian ini bertujuan untuk mengetahui pengaruh interaksi antara perlakuan pemanasan denganmetode dry heat treatment dan pemberian zat pengatur tumbuh giberelin terhadap pemecahan dormansi kelapasawit. Percobaan dilakukan menggunakan rancangan acak kelompok faktorial dengan 2 faktor, yaitu 3 taraf lamadry heat treatment (40 hari, 50 hari, 60 hari) dan 3 taraf konsentrasi giberelin (0 ppm, 100 ppm, 200 ppm) yangdiulang sebanyak 3 kali. Hasil penelitian menunjukkan tidak terdapat pengaruh interaksi antara lama dry heattreatment dan konsentrasi giberelin terhadap pemecahan dormansi kelapa sawit. Perlakuan lama dry heat treatment50 dan 60 hari berpengaruh baik pada variabel persentase perkecambahan dan indeks vigor serta panjang radikuladan panjang plumula. Konsentrasi giberelin 100 dan 200 ppm berpengaruh baik pada variabel persentaseperkecambahan, indeks vigor, panjang radikula dan panjang plumula. Lama dry-heat treatment 50 hari dankonsentrasi giberelin 100 ppm memberikan pengaruh paling efektif daripada kombinasi perlakuan lain.Kata kunci : dormansi, Dry-heat treatment, giberelin, kelapa sawit